2016
DOI: 10.1111/nph.14356
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting pollination declines through DNA barcoding: the potential contributions of macroecological and macroevolutionary scales of inquiry

Abstract: SummaryWhile pollinators are widely acknowledged as important contributors to seed production in plant communities, we do not yet have a good understanding of the importance of pollinator specialists for this ecosystem service. Determination of the prevalence of pollinator specialists is often hindered by the occurrence of cryptic species and the limitations of observational data on pollinator visitation rates, two areas where DNA barcoding of pollinators and pollen can be useful. Further, the demonstrated ade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 90 publications
(127 reference statements)
1
16
0
Order By: Relevance
“…Metabarcoding is also being used for increasingly novel applications, such as the study of trophic interactions, either through direct analyses of gut contents, or via the reconstruction of networks of multi-trophic assemblages (Bohan et al, 2017). Other fields of research such as metacommunity theory (Miller et al, 2018), and ecosystem function relationships (Vamosi et al, 2017) also benefit where previously the statistical relationships were obscured by coarse taxonomic resolution. These applications could generate substantial added value to existing or future biomonitoring programs (Compson et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Metabarcoding is also being used for increasingly novel applications, such as the study of trophic interactions, either through direct analyses of gut contents, or via the reconstruction of networks of multi-trophic assemblages (Bohan et al, 2017). Other fields of research such as metacommunity theory (Miller et al, 2018), and ecosystem function relationships (Vamosi et al, 2017) also benefit where previously the statistical relationships were obscured by coarse taxonomic resolution. These applications could generate substantial added value to existing or future biomonitoring programs (Compson et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…We investigated pollinator food niches and networks by using DNA metabarcoding data that were obtained in a previous study at the site (Pornon, Andalo, Burrus, & Escaravage, 2017). Metabarcoding has already been shown in several studies to successfully identify plant taxa in pollen mixtures (Cornman, Otto, Iwanowicz, & Pettis, 2015;Galimberti et al, 2014;Galliot et al, 2017;Lucas et al, 2018;Macgregor et al, 2019;Pornon et al, 2016;Richardson et al, 2019) at a higher taxonomic resolution than microscopy (Vamosi, Gong, Adamowicz, & Packer, 2017). A recent meta-analysis (Lamb et al, 2018) concluded on a significant quantitative positive linear relationship between the proportion of sequence reads and the proportion of species in original mixtures from very different origins (stomach contents, feces, airborne pollen, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…Once established, such databases can become a valuable toolkit for molecular ecologists to identify plant material such as pollen, seeds, seedlings, roots, and even bark fragments (Liu et al, 2018). DNA barcoding is now becoming essential for a broad range of ecological applications, such as biodiversity assessments (Lahaye et al, 2008;Yoccoz et al, 2012), establishing pollination networks (Bell et al, 2016;Vamosi, Gong, Adamowicz & Packer, 2017), diet analysis (Kartzinel et al, 2015;Valentini, Pompanon & Taberlet, 2009), and determining the mechanisms underlying community assembly (Kress et al, 2009(Kress et al, , 2010Pei et al, 2011).…”
Section: Introductionmentioning
confidence: 99%